Shedding New Lights Into STED Microscopy: Emerging Nanoprobes for Imaging - Liu, Yanfeng; Peng, Zheng; Peng, Xiao; Yan, Wei; Yang, Zhigang; Qu, Junle (Frontiers in Chemistry, 2021)
Stimulated emission depletion (STED) microscopy has long been regarded as a powerful tool for real-time super-resolved bio-imaging, since it was firstly reported in 1994. However, high STED light power (101~3 MW/cm2) is often required to achieve significant resolution improvement, which inevitably introduce photo-toxicity and severe photo-bleaching, damaging the imaging quality, especially for long-term cases. Recently, the employment of nano-probes (quantum dots, upconversion nanoparticles, carbon dots, polymer dots, AIE dots, etc) in STED imaging has brought opportunities to overcoming such long-existing issues. These nanomaterials designed for STED imaging show not only lower STED power requirements, but also more efficient photoluminescence (PL) and enhanced photo-stability compared with organic molecular probes. Herein, we review the recent progress in the development of nano-probes for STED imaging, to highlight their potential in improving the long-term imaging quality of STED microscopy and broadening its application scope. We also discuss the pros and cons for specific classes of nano-probes for STED bio-imaging in details, so as to provide practical references for biological researchers seeking for suitable imaging kits, promoting the development of relative research field.